1986
DOI: 10.3758/bf03200078
|View full text |Cite
|
Sign up to set email alerts
|

Does contextual change determine long-term forgetting?

Abstract: A series of experiments were run to test the hypothesis that "spontaneous forgetting" could result from subtle contextual changes. The first experiment demonstrated that when SpragueDawley male rats are trained in a runway alley with a food reinforcer, retention performance is dramatically affected by a change in the pattern of the walls of the training apparatus when testing takes place 1, 3, or 5 days following training and not after 1 week. Experiment 2 demonstrated that this performance deficit cannot be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 30 publications
7
39
2
Order By: Relevance
“…However, it is worth noting that our interpretation in terms of a dual function of these cues is in accordance with other data suggesting that they may influence retrieval through processes other than simple reactivation (Gisquet-Verrier & Alexinsky, 1986;Gordon, 1983;Riccio et al, 1984). For instance, if a conflicting memory is reactivated concurrently with the target memory, an additional process has to be inferred in order to account for correct retention performance.…”
Section: Pretest Cuing and Control Of Behaviorsupporting
confidence: 60%
See 2 more Smart Citations
“…However, it is worth noting that our interpretation in terms of a dual function of these cues is in accordance with other data suggesting that they may influence retrieval through processes other than simple reactivation (Gisquet-Verrier & Alexinsky, 1986;Gordon, 1983;Riccio et al, 1984). For instance, if a conflicting memory is reactivated concurrently with the target memory, an additional process has to be inferred in order to account for correct retention performance.…”
Section: Pretest Cuing and Control Of Behaviorsupporting
confidence: 60%
“…Such an effect was obtained-at least, undoubtedly, when the tone had previously been associated with active-avoidance training-even though the critical cue (the tone) was no longer present in the test context. Typically, contextual cues presented as reminders are also present at subsequent testing (but see Gibling & Davies, 1988;Gisquet-Verrier & Alexinsky, 1986). In our experiments, it appears that the pretest presentation of a unitary contextual cue (the tone) in a general context (the experimental room) induces processes that preclude those otherwise induced by the general contextual information present at the time of testing.…”
Section: Pretest Cuing and Control Of Behaviormentioning
confidence: 87%
See 1 more Smart Citation
“…Pretest exposure to the experimental context in which discriminative avoidance training had taken place also alleviates forgetting. These experiments compared the effectiveness of the contextual cue and the conditioned stimulus (CS) as reminders and found that pretest priming with the CS facilitated performance at short training to test intervals, whereas the contextual cue was only effective after a long retention interval, when control animals showed considerable forgetting (Gisquet-Verrier and Alexinsky 1986;Gisquet-Verrier et al 1989). (Left) Number of errors at each daily trial during acquisition; (right) retention performance of rats tested 3 weeks after the last training trial.…”
Section: Memory Retrieval Facilitation After Forgetting: Contextual Cmentioning
confidence: 99%
“…There is considerable evidence indicating that an exposure to some components of a learning episode can alleviate a performance decrement resulting from experimentally induced amnesia (Koppenaal, Jagoda, & Cruce, 1967; R. R. Miller & Springer, 1972;Sara, 1973a), spontaneous decrease in performance (Kamin effect: Klein & Spear, 1970;Gisquet-Verrier & Alexinsky , 1990a) , short retention intervals (Gordon & Feldman, 1978) or long-term forgetting (Deweer, Sara, & Hars, 1980;Gisquet-Verrier & Alexinsky, 1986;GisquetVerrier, Dekeyne, & Alexinsky, 1989). The facilitative effect of prior cuing is a highly reliable phenomenon that has been found in many different species, such as rats, mice, and pigeons (Moye & Thomas, 1982), as well as in human infants (Rovee-Collier & Hayne, 1987).…”
mentioning
confidence: 99%